Multidisciplinary management of a patient with eyelid ecthyma gangrenosum due to Pseudomonas aeruginosa infection (Indian Journal of Case Reports, 2024)
Pseudomonas aeruginosa is a Gram-negative bacillus, responsible for frequently serious infections that cause high morbidity and mortality, especially in immunosuppressed hosts or with underlying malignant processes. Ecthyma gangrenosum is a highly suggestive, though not pathognomonic, manifestation of disseminated P. aeruginosa infection. The palpebral presentation of the latter is estimated to be <6%, so initial clinical suspicion and early multidisciplinary management are of great importance. This article aims to show the diagnostic and therapeutic challenge of a patient who abruptly presents septicemia by Pseudomonas, accompanied by severe periocular skin symptoms in a tertiary hospital.